Decrypting the Mitochondrial Gene Pool of Modern Panamanians - Perego, Ugo A.; Lancioni, Hovirag; Tribaldos, Maribel; Angerhofer, Norman; Ekins, Jayne E.; Olivieri, Anna; Woodward, Scott R.; Pascale, Juan Miguel; Cooke, Richard; Motta, Jorge; Achilli, Alessandro (PLOS ONE, 2012)
The Isthmus of Panama–the narrow neck of land connecting the northern and southern American landmasses–was an obligatory corridor for the Paleo-Indians as they moved into South America. Archaeological evidence suggests an unbroken link between modern natives and their Paleo-Indian ancestors in some areas of Panama, even if the surviving indigenous groups account for only 12.3% of the total population. To evaluate if modern Panamanians have retained a larger fraction of the native pre-Columbian gene pool in their maternally-inherited mitochondrial genome, DNA samples and historical records were collected from more than 1500 volunteer participants living in the nine provinces and four indigenous territories of the Republic. Due to recent gene-flow, we detected ∼14% African mitochondrial lineages, confirming the demographic impact of the Atlantic slave trade and subsequent African immigration into Panama from Caribbean islands, and a small European (∼2%) component, indicating only a minor influence of colonialism on the maternal side. The majority (∼83%) of Panamanian mtDNAs clustered into native pan-American lineages, mostly represented by haplogroup A2 (51%). These findings reveal an overwhelming native maternal legacy in today's Panama, which is in contrast with the overall concept of personal identity shared by many Panamanians. Moreover, the A2 sub-clades A2ad and A2af (with the previously named 6 bp Huetar deletion), when analyzed at the maximum level of resolution (26 entire mitochondrial genomes), confirm the major role of the Pacific coastal path in the peopling of North, Central and South America, and testify to the antiquity of native mitochondrial genomes in Panama.